Let p=x^2-7p=x 2 −7p, equals, x, squared, minus, 7. Which equation is equivalent to (x^2-7)^2-4x^2+28=5(x 2 −7) 2 −4x 2 +28=5left parenthesis, x, squared, minus, 7, right parenthesis, squared, minus, 4, x, squared, plus, 28, equals, 5 in terms of ppp ? Choose 1 Choose 1 (Choice A) A p^2+4p-5=0p 2 +4p−5=0p, squared, plus, 4, p, minus, 5, equals, 0 (Choice B) B p^2-4p+23=0p 2 −4p+23=0p, squared, minus, 4, p, plus, 23, equals, 0 (Choice C) C p^2-4p-5=0p 2 −4p−5=0p, squared, minus, 4, p, minus, 5, equals, 0 (Choice D) D p^2+4p+23=0p 2 +4p+23=0 Help Plz

The answer would be (c)

B (2m^3−4p^5)(2m^3+4p^5)

Step-by-step explanation:

The factoring of the difference of squares is the product of the sum and difference of the squared terms.

... a² -b² = (a -b)(a +b)

Here, you have ...

a = 2m^3b = 4p^5

So, the factoring is the product of the sum and difference of these values:

... (2m^3 -4p^5)(2m^3 +4p^5) . . . . . . matches selection B

Comment on answer choices

Perhaps you noticed that choices A and C are the same.

A, 4p + 4 = 4 + 4p. Hope this helped.